The letter of the law. History of the constitutions of Peru. Carlos Ramos Núñez (2018) Centro de Estudios Constitucionales del Tribunal Constitucional, Lima, 112 pp. - Rodríguez Gómez, Edgardo (2018)
The magistrate of the Constitutional Tribunal Carlos Ramos Núñez, a scholar -of early vocation- of the country's legal history, offers another clear example of his research interest by publishing a brief text of classic tour through the twelve republican constitutions of the Peruvian State, which in their respective periods of validity sought to be involved as frameworks of coexistence for a complex, diverse and scarcely committed to its premises of freedom and equality -even formal- as the Peruvian society.